2012
DOI: 10.1128/iai.06224-11
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13 Exposure Enhances Vitamin D-Mediated Expression of the Human Cathelicidin Antimicrobial Peptide 18/LL-37 in Bronchial Epithelial Cells

Abstract: 25D 3 ), by CYP27B1. Low circulating vitamin D levels in childhood asthma are associated with more-severe exacerbations, which are often associated with infections. Atopic asthma is accompanied by Th2-driven inflammation mediated by cytokines such as interleukin 4 (IL-4) and IL-13, and the effect of these cytokines on vitamin D metabolism and hCAP18/LL-37 expression is unknown. Therefore, we investigated this with well-differentiated bronchial epithelial cells. To this end, cells were treated with IL-13 with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 60 publications
1
40
0
1
Order By: Relevance
“…In this respect, at least four mechanisms are known to regulate 1, 25[OH] 2 D activity. These are production of the active 1α-hydroxylated hormone by CYP27B1 [11,31,36], generation of relatively inactive 24α-hydroxylated metabolites by the action of CYP24A1 [31], sequestration by vitamin D-binding protein (VDBP) [37] and expression levels of the VDR [38]. We were interested in the regulation of vitamin D modulation of DC function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, at least four mechanisms are known to regulate 1, 25[OH] 2 D activity. These are production of the active 1α-hydroxylated hormone by CYP27B1 [11,31,36], generation of relatively inactive 24α-hydroxylated metabolites by the action of CYP24A1 [31], sequestration by vitamin D-binding protein (VDBP) [37] and expression levels of the VDR [38]. We were interested in the regulation of vitamin D modulation of DC function.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, at least four mechanisms are known to regulate 1,25[OH] 2 D activity. These are production of the active 1α-hydroxylated hormone by CYP27B1 [11,31,36] concentrations required to induce cellular responses, but the concentration of VDBP that may operate at the level of tissue-resident macrophages or DCs is not known, and data from VDBP-null mice suggests that the presence or absence of VDBP does not appear to modulate vitamin D activity in vivo [39]. Therefore, we did not investigate the role VDBP in the present model, which requires further consideration in future studies.…”
mentioning
confidence: 99%
“…On the other hand, the Th2 cytokine IL-4 induces CYP24A1 expression which leads to the catabolism of 25(OH)D 3 and downregulation of CAMP expression (Edfeldt et al 2010 ). In contrast, the Th2 cytokine IL-13 enhances CAMP expression by 25(OH)D 3 due to increased CYP27B1 expression and synthesis of 1,25(OH) 2 D 3 (Schrumpf et al 2012 ). No effect is observed with IL-17 in monocytes, but in the presence of 1,25(OH) 2 D 3 , IL-17 enhances CAMP expression in human keratinocytes via activation of the Act1 and MEK/ERK pathway (Peric et al 2008 ).…”
Section: Cooperative Induction Of Antimicrobial Peptide Gene Expressimentioning
confidence: 99%
“…More than 100 years ago, it was also observed that sun exposure was an effective treatment for cutaneous tuberculosis (Niels Finsen received the Nobel Prize in 1903 for this discovery), which was later explained by the requirement of sun exposure for the synthesis of vitamin D . More recent discoveries have elucidated that vitamin D exerts many of its protective functions by increasing the secretion of LL‐37 . LL‐37 has a defined vitamin D dependent mechanism, in that adequate circulating concentrations of its hydroxylated form 25(OH)D are required for optimal cathelicidin production by macrophages, and costimulation of 25(OH)D and TLR ligands leads to the induction of cathelicidin and killing of intracellular pathogens .…”
Section: Relevance For Human Diseasementioning
confidence: 99%